(untitled) (Mwanga wa Lugha, 2021)
This paper discusses nihilism and postproverbials as exhibited, and how occasionally they occur pari passu, in a postmodern Swahili anthology of Dhifa, published in 2008 and authored by Euphrase Kezilahabi. Nihilism is “the radical repudiation of value, meaning and desirability” (Nietzsche Friedrich 7). It is a doctrine of skepticism that negates among others, idealism, mythology, arbitrary morality, and sacred values while maintaining that established institutions based on these beliefs must be destroyed. It is a populist notion and a philosophical orientation that interrogates the meaning of life and sees life as being hopeless and meaningless. On the other hand, postproverbials are “radicalized proverbial utterances which subvert the logic and the pattern of conventional proverbs, and aim to supplement an essentially traditionalist imagination with an iconographic and modernist consciousness” (Raji-Oyelade Aderemi 49). Both forms aim to repudiate or subvert the established mantra or ethos. Justification for our contention of the proposed point of convergence between these strands is demonstrated in the innovative manipulation of Swahili proverbial logics and symbolism by Kezilahabi in his many works, and in particular, Dhifa. We present evidence of how Kezilahabi turns the conventional form of Swahili proverbs which normally serves as a vital medium to prescribe and proscribe the code of conduct of the people around to postproverbials, which are in essence, structured in a more unconventional form. Kezilahabi uses the same path to advocate his new beliefs, and values them through postproverbials or anti-proverbs. We are determined to show in this paper that the use of postproverbials is a key weapon that Kezilahabi harbours in his anti-platitudinous maneuvering to precisely drive his agenda. Our rationale is derived from parallelism we noted between Dhifa and Thus Spoke Zarathustra (1883-1885) by Friedrich Nietzsche (2006).